The observation of everyday life (2014)
After attempting to paint the multiple beings inhabiting the oral history of his Bora and Uitoto ancestors, Brus Rubio found in the daily gestures of the men and women of his community, a technique of observation and reproduction of moving figures of his own, suited to express his perception of the history of the peoples of the Ampiyacu River.